2001
DOI: 10.1007/s15010-001-1158-y
|View full text |Cite
|
Sign up to set email alerts
|

The Penetration of Ciprofloxacin into Human Pancreatic and Peripancreatic Necroses in Acute Necrotizing Pancreatitis

Abstract: Due to its antimicrobial spectrum and the good penetration into the relevant compartments, CIP may be useful in preventing local infection in necrotizing pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
2
12
0
2
Order By: Relevance
“…The species of the bacteria isolated in the study complies with those reported in the literature [5,8,27] . Antibiotic administration was initiated six hours after induction of AP, since necrosis was reported to become apparent within this period [9] .…”
Section: Discussionsupporting
confidence: 83%
“…The species of the bacteria isolated in the study complies with those reported in the literature [5,8,27] . Antibiotic administration was initiated six hours after induction of AP, since necrosis was reported to become apparent within this period [9] .…”
Section: Discussionsupporting
confidence: 83%
“…Some fluoroquinolones, e.g. ciprofloxacin, penetrate pancreatic as well as necrotic tissue sufficiently, with tissue concentrations above the corresponding serum levels, as we were able to demonstrate in our own studies [12].…”
Section: Introductionsupporting
confidence: 76%
“…Fluoroquinolones are known to penetrate the pancreas sufficiently to reach high tissue concentrations [12]. Older quinolones such as ciprofloxacin and ofloxacin were therefore the drugs of choice for the treatment of pancreatic infections.…”
Section: Discussionmentioning
confidence: 99%
“…2 In the pancreatic field, ciprofloxacin can be a useful tool as an empirical therapy in necrotizing pancreatitis to prevent secondary bacterial infection, [8][9][10][11] because ciprofloxacin penetrates the human pancreas very well. 12,13 However, ironically, it is claimed that the ciprofloxacin can, in rare cases, cause drug-induced pancreatitis. Until now, there has only been one case report associated with ciprofloxacin in the literature.…”
Section: Discussionmentioning
confidence: 99%